PP.08.19: NON-INVASIVE HAEMODYNAMIC PROFILE OF DIFFICULT TO TREAT HYPERTENSIVE PATIENTS. (June 2015) - Martinez, F.; Calaforra, O.; Solaz, E.; Vicente, A.; Pichler, G.; Martínez-Sober, M.; Soria-Olivas, E.; Redon, J.
Abstract : Objective: The haemodynamic profile (HP) can be determined non-invasively by means of thoracic electric bio-impedance (TEB).: Characterize the HP of resistant or difficult to treat hypertensive patients. Analyse the changes in HP with switching positions. Correlate changes in HP with BP changes after including eplerenone (E) to the treatment. Design and method: Sample: 27 patients with uncontrolled hypertension (UH) (mean age 57.7y; 6 female; BMI 30.8 kg/m2, average of antihypertensive drugs: 4); 16 patients with TEB study repeated after E treatment. TEB was assessed with HOTMAN® system. Changes in hemodynamic modulators are expressed as the percentage of deviation from normal (0 ± 20%). The paired ttest was used to compare changes in HP with switching positions and before and after the introduction of E. Results: The average of the main haemodynamic modulators in supine were: 61% hypervolemia; 12.9% hypochronotropism; 20.1% hypoinotropism and 34.6% vasoconstriction. When switching position from supine to sitting up, there were highly significant decreases in chronotropism (C) and inotropismo (I), highly significant increase in vasoconstriction (VC) whereas there were not significant changes in volume status (VS). From supine to upright position, there were significant decreases especially in VS but also for C and I. There was a significant increase in VC. From sitting up to upright position, there was a significant decrease in VS. There was a trend to increase the C and I but no significant changes were seen in VC. Figure. No caption available. After the addition of eplerenone, there was a significant decrease in office BP, especially for SBP (167.1 to 148.9 mmHg, p-value = 0.008) but also for DBP (96.2 to 87.7 mmHg, p-value = 0.032). There were not any significant changes in haemodynamic parameters although there was trend to decrease in VS. There were significant positive correlations among changes in SBP with VS and with VC. Conclusions: According to our results, UH is characterized mainly by hypervolemia and VC. With the BP reduction during the follow-up, there was a trend to a reduction in volume status and in the left stroke work index. The changes in BP seem to act mainly through changes in VS or VC.